Chitosan nanoparticle of hCG (Human Chorionic Gonadotrophin) hormone in increasing induction of dairy cattle ovulation - Fitra Aji Pamungkas; Ria Sari Gail Sianturi; Elizabeth Wina; Diana Andrianita Kusumaningrum (Jurnal Ilmu Ternak dan Veteriner, 2016)
A controlled release delivery system of human chorionic gonadotropin (hCG) hormone helps to overcome the rapid degradation of hCG hormone in the blood, to avoid the use of multiple injections for ovulation induction and to enhance reproductive efficacy. This study aimed to prepare chitosan nanoparticles hCG (CS-NPh) and to determine its efficacy as nasal spray of CS-NPh. The observed parameters include physico-chemical characteristics of CS-NPh and the follicle size, corpus luteum, the time of ovulation and onset of estrus performed after administration of CS-NPh as a nasal spray compared with intramuscular hCG (control) at a dose of 1,000 IU in dairy cattle. The result showed that the formation of the hormone hCG nanoparticles is still in the size range of nanoparticles with a well and more stable molecular mass distribution, so it can be used as a carrier component of hormones. The result showed that the time of ovulation after hCG by intramuscular (day to 3.13±0.35) and CS-NPh as a nasal spray (days to 3.33±0.49) with the follicle size by 1.62±0.22 and 1.76±0.28 cm showed no significant differences (p> 0.05), likewise the size of the corpus luteum and onset of oestrus. This indicates that administration of CS-NPh as a nasal spray can be used in enhancing the induction of ovulation in dairy cattles.Key Words: Nanoparticles, hCG, Nasal Spray, Ovulation